Impact Of COVID-19 Pandemic On Ophthalmology Residency Training- A Cross-Sectional Survey Among Pakistani Residents - Shaheer, Muhammad; Rafique, Asima (Journal of Rawalpindi Medical College, 2023)
Background: The purpose of this study was to get an idea of the impact of COVID-19 on Ophthalmology post-graduate training. Materials & methods: This cross-sectional questionnaire-based study was conducted at the College of Ophthalmology and Allied Vision Sciences/Eye Unit III (King Edward Medical University), Lahore from 01-03-2021 to 31-08-2021. A web-based close-ended questionnaire (Google form) was developed consisting of questions related to residency training in the wake of the COVID-19 pandemic. Eighty-one Ophthalmology residents from across the country participated in this survey. Based on the responses to 21 questions, percentages of various variables in questions were calculated. Data analysis was done on SPSS version 22. Responses to questions are mainly presented as percentages. A chi-square test was applied to see the significant difference in survey questions. For categorical variables, Fisher’s Exact test was applied. P-value ≤0.05 is considered significant. Results: Twenty-seven ophthalmology residents were 1st year residents 23 were 2nd year residents while 3rd and 4th year residents were 14 and 17 respectively. 33% of residents thought their surgical training was affected badly due to covid-19 pandemic while 55% of them were concerned about their basic cataract surgery skills. 67% of residents were in favour of their training extension for 6-12 months. The majority of residents stated that COVID-19 affected their training adversely (p=0.000) and cataract surgery training was the most affected one (p=0.000) Conclusion: The COVID-19 pandemic has severely affected the clinical and surgical training of post-graduate ophthalmology residents. Formulation of institution-based & nationwide short and long-term strategies regarding web-based teaching, surgical simulation courses and necessary adjustments in curriculum are the need of the hour.